ANALISIS SENGKETA KEPEMILIKAN AMBALAT ANTARA INDONESIA DAN MALAYSIA DALAM PRESPEKTIF SIYASAH DUSTURIYAH - Sya'dullah (The Republic : Journal of Constitutional Law, 2023)
The Ambalat Block belongs to Indonesia, this is based on evidence of the signing of the Indonesia-Malaysia Continental Boundary Agreement on 27 October 1969, which was signed in Kuala Lumpur and then ratified on 7 November 1969. This type of research is considered normative research. The nature of this research is descriptive analytical. Data was taken from two sources, namely primary sources and secondary sources. The approaches used are statutory, historical and conceptual. The data collection method was carried out using a literature study, namely a method in the form of collecting legal materials, obtained from library books or other readings that are related to the problems of the Ambalat sea dispute and siyasah dusturiyah. The results of this research concluded that Malaysia has ignored the fact that its country is a coast and not an island nation. Maritime boundary disputes up to the resolution of disputes between Indonesia and Malaysia are regulated in Law Number 17 of 1985 and UCLOS 1983. Fiqh Siyasah regarding the Ambalat Sea territorial boundary dispute between Indonesia and Malaysia is included in the Siyasah Dusturiyah category which discusses wizarah or assistants to the Imamah which can be interpreted as the minister in charge of resolving internal and external problems within the state and as supervisor of state administration. So it can be concluded that the Minister of Defense or Wazir Amirul Jaisy in resolving cases between the State of Indonesia and the State of Malaysia regarding territorial boundary disputes in the Ambalat Sea can be resolved using the law Islam by making peace, and not separating or being hostile to each other Keywords: Ambalat, Dispute, Siyasah Dusturiyah